Offshore structure modeling - Chakrabarti, Subrata K. 1941- (World Scientific, 1994)
While the existing literature on offshore structures touch on model testing, a comprehensive text discussing the design, construction, instrumentation, testing and analysis of the physical model is lacking. This book fills that vacuum and provides, through its survey of the theoretical and practical aspects of physical modeling, an in-depth coverage of the technology of model testing. Its usefulness runs through the entire field of engineering, reaching far beyond its focus on offshore construction; and its breadth of scope should appeal not only to engineers and naval architects but to scientists interested in structural or hydraulic testing as well.
Keywords: Offshore structures -- Models.; elektronické knihy; electronic books